Translating Theory of English into Indonesian and Vice-Versa - Teti Apriyanti; Heidy Wulandari; Marita Safitri; Novita Dewi (Indonesian Journal of English Language Studies (IJELS), 2016)
The present study is aimed at providing translating theory of English into Indonesian and vice versa. In achieving the aim, content analysis of expressive (poem), informative (report and academic), and vocative text (advertisement) is applied. The analysis is based on three aspects consisting of grammatical structure, cultural words, and writing mechanic. The result shows that the translator needs to adapt the grammatical structure, cultural words, and writing mechanic of source language into target language. However, there are exceptions in cultural words and capitalization. In translating from English into Indonesian especially in academic text, some English words are assimilated into Indonesian (foreignization). In translating Indonesian poem into English, the target text capitalization imitates source text capitalization. Besides, for the purpose of attractiveness, persuasion, and effectiveness in translating Indonesian advertisement into English, different words are prefered but the meaning is retained.